Social and Work Exchange Towards Organizational Citizenship Behavior - Maria Ariesta Utha (Business and Entrepreneurial Review, 2006)
The purpose of this research is to description to the readers regarding individual attachment to his/her organization. Individual perceptions on rewards they received and on their organizations. Consequently, individuals who have good perception will possess strong attachment to the organization and will develop Organizational Citizenship Behavior (OCB). A hypothesis test was utilized to measure the perception and attachment of social and work exchange that construct OCB. The data analysis used was confirmatory analysis, whereas the sampling method was purposive or judgmental. The result of this research concluded that work perception does relate with work attachment. Social and economic perception did not have any relationship towards social and economic attachment; however it creates an organizational citizenship behavior (OCB)